Geochemical response of Aptian sediments before, during and after Oceanic Anoxic Event 1A: insight from the La Frontera section Subbetic Basin, southern Spain - Herdocia, Carlos; Maurrasse, Florentin J-M. R. (Frontiers in Earth Science, 2025)
The hallmark of lower Aptian sediments is commonly organic-rich black shales related to widespread oxygen deficient conditions known as ocean anoxic event 1a (OAE1a). The La Frontera section, located in the Subbetic Basin, southern Spain, documents the response to OAE1a within a ∼28 m interval divided into 3 units: U1 (before), U2 (during OAE1a), and U3 (after) to assess the local changes related to the global event. Analytical results include TIC, TOC, major elements (Al, Si, and Ti), biolimiting elements (Fe and P), redox sensitive trace elements (RSTEs; V, Cr, Cu, Mo, and U), clay minerals, bulk mineralogy, and biomarkers. Biomarker data from C27 hopane Ts/(Ts + Tm) ratios and C31 22S/(22S + 22R) homohopane ratios indicate that OM from this site are thermally immature. Unit 1 contains the highest TIC values with limestone layers that were deposited under well oxygenated conditions with minimal detrital input and low TOC. Recurrent marlstone layers within U1 show higher TOC related to heightened terrestrial input which provided increased biolimiting elements that sustained enhanced primary productivity. Elevated RSTE values associated with marlstone layers suggest low oxygen conditions, however without reaching full anoxia. The onset of OAE1a in U2 is marked by diminished TIC and dark shales with the highest TOC and RSTE values. Increased Al content, the presence of longer chain n-alkanes, plus increased quartz and feldspars during this interval are attributed to enhanced hydrological cycles providing more nutrients to the basin. Concurrently biolimiting elements were remobilized by reducing conditions as indicated by coeval increases in the RSTEs. U3 contains recurring peaks of TIC coincident with low TOC values and is characterized by decreases in relative abundances of quartz and feldspars, lower Al content and a shift back to only marine OM. Concurrence of these factors imply a decline in fluvial input. RSTEs in this unit are decoupled from TOC and correlate with Al, indicating a common provenance and that the bottom waters were likely oxygenated. Thus, the results of this study reveal that enhanced hydrologic cycles was the main driving mechanism for enhanced accumulation and preservation of OM during OAE1a in the Subbetic Basin.